2019
DOI: 10.15517/rbt.v67is5.38937
|View full text |Cite
|
Sign up to set email alerts
|

Polychaetes from Burdwood Bank: “Namuncurá I” Marine Protected Area and slope, SW Atlantic Ocean

Abstract: Introduction: The first open-sea (non-coastal) Marine Protected Area in Argentina, named “Namuncurá I” (NMPA), was created in 2013 at Burdwood Bank (BB), an undersea plateau located about 200 km south from Malvinas Islands (Falkland Islands) and 150 km east from Staten Island, SW Atlantic Ocean. It comprises three different management areas: the central one (“core”, strict protection, only control and monitoring activities), surrounded by a “buffer” area (authorized activities, e.g. scientific research) and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Nonetheless, the benthic communities found on the Burdwood Bank slope are similar to those described for northern sectors on the Argentinean slope (see Portela et al, , ; Schejter et al, ), which evidences a continuous habitat in which the Malvinas (Falkland) Current flows. Some important results obtained from the study of the samples taken during the Argentinean research cruises between 2013 and 2018 are the inventories of ascidians (Taverna et al, ), Asteroidea (Fraysse, Calcagno, & Pérez, ), brachiopods (Gordillo, Bayer, de Aranzamendi, Taverna, & Morán, ), molluscs (Di Luca & Zelaya, ), and polychaetes (Bremec et al, ), and the distribution and reproduction of some fishes have been also reported by García Alonso, Brown, Martín, Pájaro, and Capitanio (). Several new species have also been discovered in this area (Schejter, Bertolino, & Calcinai, ; Güller & Zelaya, ; Urcola & Zelaya, ; López Gappa, Liuzzi, & Zelaya, ), and many more are undergoing the description process.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the benthic communities found on the Burdwood Bank slope are similar to those described for northern sectors on the Argentinean slope (see Portela et al, , ; Schejter et al, ), which evidences a continuous habitat in which the Malvinas (Falkland) Current flows. Some important results obtained from the study of the samples taken during the Argentinean research cruises between 2013 and 2018 are the inventories of ascidians (Taverna et al, ), Asteroidea (Fraysse, Calcagno, & Pérez, ), brachiopods (Gordillo, Bayer, de Aranzamendi, Taverna, & Morán, ), molluscs (Di Luca & Zelaya, ), and polychaetes (Bremec et al, ), and the distribution and reproduction of some fishes have been also reported by García Alonso, Brown, Martín, Pájaro, and Capitanio (). Several new species have also been discovered in this area (Schejter, Bertolino, & Calcinai, ; Güller & Zelaya, ; Urcola & Zelaya, ; López Gappa, Liuzzi, & Zelaya, ), and many more are undergoing the description process.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all the species (except Abyssianira dentifrons) reported from Burdwood Bank are also present in the Magellan Region (see Table 3). It is worth noticing that high faunal affinities between Burdwood Bank and the Magellan Region have also been reported for other taxa, such as mollusks, bryozoans, polychaetes, decapods, and amphipods (Linse et al 2003;Romero et al 2003;Lovrich et al 2005;Moyano 2005;De Broyer and Jażdżewska 2014;Bremec et al 2019). These results suggest that the West and North channels that separate Burdwood Bank from the Argentine Continental Shelf do not form an effective barrier to species dispersion and gene flow.…”
Section: Biogeography Endemism and Mechanisms Of Species Dispersionmentioning
confidence: 94%
“…In addition, exhaustive species inventories, descriptions of new species, new records of distribution, and studies on reproductive biology and biogeography have been recently published on the fauna from Burdwood Bank (Güller and Zelaya 2017; Penchaszadeh et al 2017Penchaszadeh et al , 2019Schejter et al 2017a;Fraysse et al 2018Fraysse et al , 2020García Alonso et al 2018;López Gappa et al 2018;Taverna et al 2018;Urcola and Zelaya 2018;Bremec et al 2019;Di Luca and Zelaya 2019;Gordillo et al 2019;Teso and Penchaszadeh 2019;Pérez-Barros et al 2020;Roccatagliata 2020;among others).…”
Section: Introductionmentioning
confidence: 99%
“…For invertebrates other than decapod crustaceans, the role of the BB on their distribution is variable. For example, in the BB, isopods, cumaceans, polychaetes, or bryozoans are typically Magellanic [26][27][28], whereas asteroids have higher richness at the BB than off the Atlantic coast of southern South America [29]. The distribution of molluscs, one of the most diverse groups at the BB, is controversial according to different authors: they are likely segregated by depth, distributed according to water masses and extending their distribution northwards through deep, cold waters [30], or the BB could be a place for endemism for some groups [31].…”
Section: Introductionmentioning
confidence: 99%